Psychosocial problems and quality of life in children with chronic kidney disease - Damri, Thawatchai; Louthrenoo, Orawan; Chartapisak, Wattana; Opastirakul, Sauwalak (Biomedical Sciences and Clinical Medicine, 2024)
Objectives To assess psychosocial problems in children with chronic kidney disease (CKD) by comparing them with controls and to ascertain the relationship between psychosocial problems and quality of life in these children. Method A cross-sectional study of children with CKD and healthy children was conducted. The Strengths and Difficulties Questionnaire (SDQ) and the Pediatric Quality of Life (PedsQL) were used to assess psychosocial problems and quality of life, respectively. Self-report and parentreport forms of the SDQ and the PedsQL were completed by children and parents from both groups. Results Twenty-five CKD patients and 25 healthy controls were enrolled into this study. The major causes of CKD were congenital nephro-uropathies and glomerular diseases. The mean SDQ self-report scores, especially emotional symptoms, of children with CKD were significantly higher than those of controls (p= 0.02). The SDQ scores in the CKD group, reported by parents, were higher in many domains, especially the total score and emotional symptoms (p=0.02 and 0.01, respectively). The PedsQL scores from parent reports in the CKD group were significantly lower than those of the controls, especially the total, psychosocial, and social scores (p=0.01, 0.02 and 0.01 respectively). The relationship between psychosocial problems and quality of life in children with CKD was fair and correlated negatively (r=-0.47, p< 0.05). Conclusion Children with CKD were at increased risk of psychosocial problems, especially emotional problems, and they tended to have lower quality of life. Appropriate psychosocial intervention may be needed for a better treatment outcome and quality of life for successful transition into adulthood.